Model Law for the Management of Public Land for Common Use - Yuttitham, Anchan; Mallikamarn, Sunee (Journal for Developing the Social and Community, 2021)
The objective of this research is to propose propose a draft of a model law on public land management for citizens. In addition, the draft of the model law is the result of a study which has two main points related to public land management. The first issue about the problems and the effects of the current legal system which is applied to manage the public land in Thailand and the next issue is a study and an analysis of foreign legal systems used for the management of public lands.This research approach is consisted of documentary research, in-depth interviews meanwhile opinions of the stakeholders are heard and they also directly engage in the process of designing the model law. The research found that Thailand does not have any law specifically used to manage public land such as there are no details of a law that have measures to protect and manage public land for the citizens of the country. The results of lacking law used in public land management are many spaces of public land are abandoned and misused which affect public utility of public land usage in the country. As a result, this research proposes a model law used in public land management for common citizens. The structure of the model law has 5 chapters, consisting of chapter 1 General provisions, chapter public land management committee, chapter 3 management of public land ,chapter 4,Promotion measures and chapter 5 Punishment. This research also suggests that there should be researches on “measures of making the model law used in public land management for common citizens taking effect” so the public land is used properly for fulfilling its purposes.